2020
DOI: 10.1111/1751-7915.13575
|View full text |Cite
|
Sign up to set email alerts
|

Stochasticity in microbiology: managing unpredictability to reach the Sustainable Development Goals

Abstract: Summary Pure (single) cultures of microorganisms and mixed microbial communities (microbiomes) have been important for centuries in providing renewable energy, clean water and food products to human society and will continue to play a crucial role to pursue the Sustainable Development Goals. To use microorganisms effectively, microbial engineered processes require adequate control. Microbial communities are shaped by manageable deterministic processes, but also by stochastic processes, which can promote unfore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 158 publications
(187 reference statements)
0
27
0
Order By: Relevance
“…Disturbances usually involve alterations in the available resources or the biomass concentration in the given environment. To predict the consequence of disturbances on the dynamics of microbial communities , it is essential to understand how the disturbance influences the four assembly processes' relative contributions [7,10]. Some studies have shown that disturbances affect the relative contribution of the assembly processes [11,[20][21][22][23][24][25], but conclusions vary depending on the disturbance type and the ecosystem studied.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances usually involve alterations in the available resources or the biomass concentration in the given environment. To predict the consequence of disturbances on the dynamics of microbial communities , it is essential to understand how the disturbance influences the four assembly processes' relative contributions [7,10]. Some studies have shown that disturbances affect the relative contribution of the assembly processes [11,[20][21][22][23][24][25], but conclusions vary depending on the disturbance type and the ecosystem studied.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances usually involve alterations in the available resources or the biomass concentration in the given environment. To predict the consequence of disturbances on the dynamics of microbial communities, it is essential to understand how the disturbance influences the four assembly processes' relative contributions (7,10). Some studies have shown that disturbances affect the relative contribution of the assembly processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the implementation of new sustainable bio-based technologies is needed to produce clean, renewable energy and recover resources from organic waste. Despite the multitude of strategies that have been developed to valorize the energy content of organic feedstocks, anaerobic digestion (AD) still represents the most widely applied process due to its high efficiency, operational flexibility and overall environmental benefits [4,5] offered as compared to other biorefinery approaches.…”
Section: Introductionmentioning
confidence: 99%